Thieves on the fens eaudiobook - Ellis, Joy (DI Nikki Galena, 2018)
DI Nikki Galena gets a series of anonymous calls. She is told the place, time, and who will die. But the messages are in a secret language used only by villains. Nikki and her team must decode the riddles and work out where the threats are coming from. Meanwhile, the fens have been hit by a series of "designer burglaries." It appears that a new gang of thieves are stealing to order. And things get very close to home when a friend of Nikki's mother dies suddenly and perhaps suspiciously. Do any of these events relate, and can Nikki stop the thieves on the fens, before anyone else dies? Full of twists and turns, this is a crime thriller that will keep you in suspense until its heart-stopping conclusion.